Interroger les privilèges par l’expérience de l’accouchement de femmes françaises émigrées en Roumanie - Eva Renaudeau (Anthropologie & Santé, 2025)
By analysing the therapeutic trajectories of French migrant women in Romania, this article examines the notion of privilege in the light of class and gender relations. Firstly, studying French migration in Europe sheds light on the disparities between European Union nationals and questions the modalities of free movement. Secondly, the forms of social protection available to French citizens show the disparities in access to healthcare within the French community in Romania. These material conditions are linked to the intimate experience of health in migration revealing the types of vulnerability associated with this experience and raising questions about privilege. Finally, by approaching these questions through the experience of childbirth, this article seeks to analyse in detail the gendered dimension of this experience.